Profil Tegangan Beban Tidak Seimbang Pada Jaringan Distribusi Dengan Metode Pendekatan Langsung - Rafli Guswandri; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Radial distribution network has a load imbalance due to be connected directly to the consumer, so that the voltage and voltage drop is not the same thing for each phase. Several methods are utilized to analyze power flow such as; Newton Rapson and fast Decouple. The method uses the assumption of balanced load in each phase. In this study, the direct approach method will be analyzed for loads that are not balanced in the distribution system. This direct approach method have been carried out on feeders 20 kV Adi Sucipto PT. PLN (Persero) in Pekanbaru. The simulation results have shown the value of accuray with a fairly good average. The final results obtained are reflected in the value of Mean Absolute Percentage Error (MAPE) of 2.5% of the measurement voltage.Keywords: distribution system, direct approach, feeders, voltage drop, MAPE